Use of the foot-and-mouth disease virus 2A peptide co-expression system to study intracellular protein trafficking in Arabidopsis. - Stefan Burén; Cristina Ortega-Villasante; Krisztina Otvös; Göran Samuelsson; László Bakó; Arsenio Villarejo (PLoS ONE, 2012)
A tool for stoichiometric co-expression of effector and target proteins to study intracellular protein trafficking processes has been provided by the so called 2A peptide technology. In this system, the 16-20 amino acid 2A peptide from RNA viruses allows synthesis of multiple gene products from single transcripts. However, so far the use of the 2A technology in plant systems has been limited.The aim of this work was to assess the suitability of the 2A peptide technology to study the effects exerted by dominant mutant forms of three small GTPase proteins, RABD2a, SAR1, and ARF1 on intracellular protein trafficking in plant cells. Special emphasis was given to CAH1 protein from Arabidopsis, which is trafficking to the chloroplast via a poorly characterized endoplasmic reticulum-to-Golgi pathway. Dominant negative mutants for these GTPases were co-expressed with fluorescent marker proteins as polyproteins separated by a 20 residue self-cleaving 2A peptide. Cleavage efficiency analysis of the generated polyproteins showed that functionality of the 2A peptide was influenced by several factors. This enabled us to design constructs with greatly increased cleavage efficiency compared to previous studies. The dominant negative GTPase variants resulting from cleavage of these 2A peptide constructs were found to be stable and active, and were successfully used to study the inhibitory effect on trafficking of the N-glycosylated CAH1 protein through the endomembrane system.We demonstrate that the 2A peptide is a suitable tool when studying plant intracellular protein trafficking and that transient protoplast and in planta expression of mutant forms of SAR1 and RABD2a disrupts CAH1 trafficking. Similarly, expression of dominant ARF1 mutants also caused inhibition of CAH1 trafficking to a different extent. These results indicate that early trafficking of the plastid glycoprotein CAH1 depends on canonical vesicular transport mechanisms operating between the endoplasmic reticulum and Golgi apparatus.